DEN FLEKSIBLE GRÆNSE MELLEM SPISELIGT OG IKKE-SPISELIGT - Højlund, Susanne; Selmer, Bodil; Knakkergaard, Lotte; Østergaard, Jens Sejer; Dahlgaard, Vibeke; Bro, Christian Pauli (Tidsskriftet Antropologi, 2013)
Eksperimenterende feltarbejde i et kulinarisk grænseland